Mandatory integration agreements for unemployed job seekers: A randomized controlled field experiment in Germany - Gerard J. van den Berg; Barbara Hofmann; Gesine Stephan; Arne Uhlendorff (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2021)
Integration Agreement (IA) are contracts between the employment agency and the unemployed, nudging the latter to comply with rules on search behavior. We designed and implemented an RCT involving thousands of newly unemployed workers, randomizing at the individual level both the timing of the IA and whether it is announced in advance. Administrative registers provide outcomes. Novel theoretical and methodological analyses provide tools to detect anticipation and suggest estimation by individual baseline employability. A small positive effect on entering employment is driven by individuals with adverse prospects. For them, early IA increase re-employment within a year from 45% to 53%.
Keywords: J68; J64; C93; 330; unemployment; monitoring; job search; active labor market policy; nudge; anticipation; randomized controlled trial